Kekuatan Klausula Pengaman Diri Dalam Akta Bagi Notaris - Andi Listiana (Lex Renaissance, 2020)
The purpose of this research is to identify the legal binding force of the Notary's self-security clause in the deed if there is a client who denies it and to analyse whether the self-security clause in the Partij deed can provide legal protection for Notaries in carrying out their duties and functions. This research was conducted using the empirical juridical method, namely how the law is implemented in social life. Primary data were obtained from interviews, and while the secondary ones were from literature studies and the laws. The result of the research concludes that the responsibility of the notary is limited to the formal truth in a deed. Notaries have no responsibility to judge the material truth of the information obtained from the clients. Subsequently, in the event of the party in the deed accuses or argues that the Notary has included false information in the authentic deed shall not justifiable as the Notary is not a party to the deed.